Efektivitas Media Pembelajaran Audio Visual pada Mata Pelajaran PKN Terhadap Hasil Belajar Siswa Sekolah Dasar (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
Audio-visual media commonly used in teaching and learning activities in the 21st century. The purpose of this research is to determine how effective audio-visual media is to be applied in elementary schools to improve student learning outcomes in Civics subjects in Elementary Schools. By using qualitative method with a literature study approach. The form of activity carried out is to conduct literature research through collecting data with listening techniques, participatory observation taken from Google Scholar with the keywords "Audio-visual media", "Civics Learning", "Elementary School Students", and "Learning outcomes", and data analysis. The results of the literature study of 12 scientific journals obtained are that audio-visual media is effective to be used in learning and has been proven to improve student learning outcomes.